Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1038/sj.bjc.6603833
|View full text |Cite
|
Sign up to set email alerts
|

A single institutional experience of thymic epithelial tumours over 11 years: clinical features and outcome and implications for future management

Abstract: Thymic epithelial tumours (TETs), the most common tumour of the anterior mediastinum, are epithelial neoplasms of the thymus with a wide spectrum of morphologic features. We retrospectively analysed clinical features of TET and the correlation of World Health Organisation (WHO) histologic classification and Masaoka staging system with different treatment modalities in 195 patients, from 1995 to 2005. According to the Masaoka's staging system, there were 78 (40.0 %) patients with stage I, 38 (19.5%) with stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
3
19
1
4
Order By: Relevance
“…Recently, the WHO Consensus Committee recommended that epithelial tumors of thymus be classified as thymoma, including type A, AB, B1, B2, and B3 thymoma and thymic carcinoma (29). Most of the WHO type A, AB, B1, and B2 thymomas are benign; however, types B3 and C have malignant potential (30). Our study (24) demonstrated that 16 of 140 thymomas patients experienced recurrences.…”
Section: Pathologic Classificationmentioning
confidence: 58%
“…Recently, the WHO Consensus Committee recommended that epithelial tumors of thymus be classified as thymoma, including type A, AB, B1, B2, and B3 thymoma and thymic carcinoma (29). Most of the WHO type A, AB, B1, and B2 thymomas are benign; however, types B3 and C have malignant potential (30). Our study (24) demonstrated that 16 of 140 thymomas patients experienced recurrences.…”
Section: Pathologic Classificationmentioning
confidence: 58%
“…[7,12] İlk nüks yeri plevra/perikard, akciğer olup yüksek riskli ve ileri evrede adjuvan tedavi ile nüksün önlenebileceği bildirilmektedir. [3,7] EIII-IV olgularda TE sonrası adjuvan RT önerilirken, EII olup TE timomalı olgularda adjuvan tedavi kararı-nın kötü risk faktörleri varlığında verilmesi gerektiği vurgulanmaktadır. [13][14][15][16] Sağkalım açısından invazivlik, rezeksiyon tipi, MG varlığı, ileri yaş, tümör çapı, hücre siklus protein ekspresyonu gibi birçok PF ortaya konmasına rağmen genel olarak Masaoka ve DSÖ sınıflaması en iyi ve geçerli prediktörler olarak kabul edilmekte ve adjuvan tedavi kararının PF'ye göre verilmesi gerektiği bildirilmektedir.…”
Section: Discussionunclassified
“…[13][14][15][16] Sağkalım açısından invazivlik, rezeksiyon tipi, MG varlığı, ileri yaş, tümör çapı, hücre siklus protein ekspresyonu gibi birçok PF ortaya konmasına rağmen genel olarak Masaoka ve DSÖ sınıflaması en iyi ve geçerli prediktörler olarak kabul edilmekte ve adjuvan tedavi kararının PF'ye göre verilmesi gerektiği bildirilmektedir. [1,3,[17][18][19][20] Masaoka evresine göre beş yıllık GSK EI-III timoma için %85, EIV için %65 bildirilmektedir.…”
Section: Discussionunclassified
See 2 more Smart Citations